A dose-response relationship between long working hours and unmet need for access to hospital facilities - Hongdeok Soek; Jong-Uk Won; Tae Il Lee; Yeong-Kwang Kim; Wanhyung Lee; June-Hee Lee; Jaehoon Roh; Jin-Ha Yoon (Nordic Association of Occupational Safety and Health (NOROSH), 2016)
OBJECTIVES: Lack of access to hospital facilities, indicating unmet healthcare need, plays an important role in health inequity in the workplace. We aimed to investigate the association between long working hours and unmet healthcare need. METHODS: We used data from the Korea National Health and Nutrition Examination Surveys collected during 2007-2012, which included 8369 participants (4765 males, 3604 females) aged 20-54 years, who were paid workers. We used a logistic regression model with gender stratification to investigate the association between working hours and unmet healthcare need. RESULTS: Of the 8369 participants, 855 males (17.94%) and 981 females (27.22%) experienced unmet healthcare need. After adjusting for covariates, and compared to 30-39 working hours per week, the odds ratios (OR) of unmet healthcare need were 1.07 [(95% confidence interval (95% CI) 0.76-1.51], 1.46 (95% CI 1.03-2.07), and 1.57 (95% CI 1.11-2.23) in males, and 1.13 (95% CI 0.92-1.40), 1.30 (95% CI 0.99-1.69), and 1.60 (95% CI 1.21-2.10) in females, for 40-49, 50-59, and ≥60 work hours per week, respectively. There was a dose-response relationship between working hours per week and unmet healthcare need in both genders. CONCLUSIONS: Those who work long hours are more likely to have unmet healthcare needs, the cause of which seems to be lack of time.